Optimized Parameters for Transducing the Locus Coeruleus Using Canine Adenovirus Type 2 (CAV2) Vector in Rats for Chemogenetic Modulation Research - Stevens, Latoya; Larsen, Lars Emil; Van Lysebettens, Wouter; Carrette, Evelien; Boon, Paul; Raedt, Robrecht; Vonck, Kristl (Frontiers in Neuroscience, 2021)
Introduction The locus coeruleus noradrenergic (LC-NA) system is studied for its role in various neurological and psychiatric disorders such as epilepsy and Major Depression Dissorder. Chemogenetics is a powerful technique for specific manipulation of the LC to investigate its functioning. Local injection of AAV2/7 viral vectors has limitations with regards to efficiency and specificity of the transduction, potentially due to low tropism of AAV2/7 for LC neurons. In this study we used a canine adenovirus type 2 (CAV2) vector with different volumes and viral particle numbers to achieve high and selective expression of hM3Dq, an excitatory Designer Receptor Exclusively Activated by Designer Drugs (DREADD), for chemogenetic modulation of LC neurons. Methods Adult male Sprague-Dawley rats were injected in the LC with different absolute numbers of CAV2-PRSx8-hM3Dq-mCherry physical particles (0.1E9, 1E9 , 5E9 ,10E9 or 20E9 pp) using different volumes (LowV=3x300nl, MediumV=3x600nl, HighV=3x1200nl). Two weeks post-injection, double-labelling immunohistochemistry for dopamine β hydroxylase (DBH) and mCherry was performed to determine hM3Dq expression and its specificity for LC neurons. The size of the transduced LC was compared to the contralateral LC to identify signs of toxicity. Results Administration of Medium volume (3x600nl) and 1E9 particles resulted in high expression levels with 87.3±9.8% of LC neurons expressing hM3Dq, but low selectivity with 36.2±17.3% of hM3Dq expression in non-LC neurons. The most diluted conditions (Low volume_0.1Epp and Medium Volume_0.1Epp) presented similar high transduction of LC neurons (70.9±12.7% and 77.2± 9.8%) with lower aspecificity (5.5±3.5% and 4.0±1.9% respectively). Signs of toxicity were observed in all undiluted conditions as evidenced by a decreased size of the transduced LC. Conclusion This study identified optimal conditions (Low and Medium Volume with 0.1E9 particles of CAV2-PRSx8-hM3Dq-mCherry) for safe and specific transduction of LC neurons with excitatory DREADDs to study the role of the LC-NA system in health and disease .